The association between epicardial adipose tissue and prognosis in heart failure with preserved and reduced ejection fraction. (4th February 2022) - Pugliese, NR; De Biase, N; Mazzola, M; Paneni, F; Del Punta, L; Gargani, L; Mengozzi, A; Virdis, A; Nesti, L; Taddei, S; Flammer, A; Borlaug, BA; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Recent evidence shows that increased epicardial adipose tissue (EAT) thickness is associated with metabolic syndrome, microvascular dysfunction and enhanced pericardial restraint. Purpose. We measured echocardiography-derived EAT thickness in a population of heart failure (HF) patients with reduced (HFrEF) and preserved (HFpEF) ejection fraction to examine the relationship between EAT and prognosis at clinical follow-up. Methods. We prospectively enrolled 393 consecutive HF outpatients  (205 HFrEF, 188 HFpEF) who had been referred to our hospital due to dyspnoea and/or effort intolerance. We performed a resting clinical and biohumoral evaluation,  followed by combined cardiopulmonary-echocardiography exercise stress. We considered a composite endpoint of cardiovascular death and HF-related hospitalization during follow-up. Results. Patients with HFpEF displayed greater EAT thickness (median 8 mm, interquartile range [IQR] 4–12 mm) than HFrEF (median 3 mm, IQR 2–6 mm; p < 0.0001).  During a median follow-up of 20.9 months (IQR 15-25 months), 34 cardiovascular deaths and 146 HF hospitalizations were reported,  with no significant differences between the two HF phenotypes. EAT was shown to predict adverse events independently from body mass index, waist circumference and other well-established prognostic markers in HF (such as NT-proBNP and peak oxygen consumption). The risk of adverse events increased with increasing EAT thickness in HFpEF and with EAT thinning in HFrEF. Kaplan-Meier analyses for the composite endpoint showed that in HFpEF,  the survival probability was significantly lower in patients with thicker EAT than those with thinner EAT. In HFrEF, conversely,  patients with increased EAT thickness had a higher survival probability than those with reduced EAT thickness (Figure 1). Conclusion. EAT accumulation is increased in HFpEF compared to HFrEF and carries different prognostic meanings in the two subsets. In HFpEF, EAT thickening portends adverse outcomes, which may be due to the secretion of pro-inflammatory and pro-atherogenic adipokines and increased mechanical restraint. In HFrEF,  EAT thinning is associated with a worse prognosis, probably reflecting a more advanced catabolic state (e.g.,  cardiac cachexia). Larger studies are needed to determine whether or not EAT has a causal role in influencing progression and survival in the different HF phenotypes.